2023
DOI: 10.1007/s00784-023-05073-4
|View full text |Cite
|
Sign up to set email alerts
|

Level of difficulty of tooth extractions among roughly 100,000 procedures in primary care

Abstract: Objectives The study examined treatment codes of extracted teeth and aimed to assess degree of difficulty concerning all tooth extractions. Materials and methods Retrospective data on treatment codes of all tooth extractions during a two-year period were obtained from the patient register in primary oral healthcare of the City of Helsinki, Finland. Prevalence, indication, and method of extraction appeared in the treatment codes (EBA-codes). Degree of diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It is unclear whether periodontal disease influences the risk of post-operative complications. A retrospective analysis reported that teeth with marginal periodontitis typically required an easier extraction (9%, n = 723), compared to teeth with periapical periodontitis which were deemed more complex (34%, n = 5,170) ( P < 0.001) [ 125 ]. This could have an implication for the association between extraction complexity and duration with post-operative complications [ 125 ].…”
Section: Narrative Reviewmentioning
confidence: 99%
“…It is unclear whether periodontal disease influences the risk of post-operative complications. A retrospective analysis reported that teeth with marginal periodontitis typically required an easier extraction (9%, n = 723), compared to teeth with periapical periodontitis which were deemed more complex (34%, n = 5,170) ( P < 0.001) [ 125 ]. This could have an implication for the association between extraction complexity and duration with post-operative complications [ 125 ].…”
Section: Narrative Reviewmentioning
confidence: 99%